Early and late complications of endoscopic hemostatic techniques following different carotid artery injury characteristics. Issue 8 (26th March 2014) - Padhye, Vikram; Valentine, Rowan; Paramasivan, Sathish; Jardeleza, Camille; Bassiouni, Ahmed; Vreugde, Sarah; Wormald, Peter‐John
<x xml:space="preserve">Abstract</x> Background The most dreaded hemorrhagic complication in endoscopic endonasal surgery is injury to the internal carotid artery (ICA). Although a number of treatment protocols are currently used, none have been formally investigated. This study aims to compare the efficacy of the muscle patch, bipolar diathermy, and aneurysm clip on hemostasis, pseudoaneurysm formation, and long‐term vessel patency for different injury types in a sheep model of carotid bleeding. Methods Twenty‐seven sheep underwent ICA dissection/isolation followed by the artery placement within a modified "sinus model otorhino neuro trainer" (SIMONT) model. Standardized linear, punch, and stellate injuries were made. Randomization of sheep to receive 1 of 3 hemostatic techniques was performed (muscle, bipolar, clip). Specific outcome measures included attainment of primary hemostasis, time to hemostasis, blood loss, pseudoaneurysm formation, and carotid patency on follow‐up magnetic resonance imaging (MRI). Results Bipolar achieved primary hemostasis in 7 of 9 cases and 2 cases of secondary hemorrhage. It had no associated pseudoaneurysm formation. Carotid patency was variable on follow‐up MRI. Muscle patch achieved 100% primary hemostasis with 2 cases of secondary hemorrhage. There were 2 cases of pseudoaneurysm and 100% patency rate on follow‐up MRI. Aneurysm clip achieved 100% primary hemostasis with 1 case of secondary hemorrhage. No pseudoaneurysm formation and a 50% rate of carotid insufficiency on MRI. Conclusion This study shows that the crushed muscle patch and aneurysm clip can be viable options in the management of ICA injury with short‐term and long‐term benefits. Complications associated with these techniques were comparable if not reduced when compared to the published literature.